The use of the coats and biosafety (Research, Society and Development, 2020)
The use of white coats aims to protect professionals when performing procedures to patients involving biological material. However, their potential for cross-infection by multidisciplinary health teams has not yet been proven, as these microorganisms require a humid environment for their survival. Thus, a review was performed on articles dealing with the use of lab coats as a means of transmission of pathogenic microorganisms. The search was performed on the PubMed®, Scielo, and Google Scholar indexed databases, and used as search strategy the terms Medical Subject Headings (MeSH): (("coats") AND ("cross infection")) OR "pathogenic microorganisms ". Full text articles published over the past 30 years (from January 1990 to December 2019) were included. The PRISMA guidelines were followed. The search resulted in 167 articles, of which 145 were excluded for not having relevance to the theme, leaving 22 articles. The study reiterates the need for awareness campaigns among professionals and the population regarding the restriction of the use of lab coats in external areas, as well as the rigorous and frequent disinfection of them.